THE EFFECTS OF EVAPORATION TIME AND ANNEALING TREATMENT ON THE FORMATION OF NICKEL CATALYST FOR CNT GROWTH - Christy Keintjem, Aveni
Due to the indium resources that start to be strictly limited and high cost of fabrication process make many scientists propose other material that can be used to replace the transparent conductive oxide (TCO) on photovoltaic (PV) device. Carbon nanotube (CNT) become one of the materials that is proposed. This condition makes the analysis related to the growth of CNT with appropriate characterization for TCO replacement applications continue to be carried out, not least the analysis related to catalyst particles as CNT growth media that has shown an important role on CNT growth results. Based on these needs, the focus of this study will be related to the growth of catalyst particles using evaporation method and formed by the annealing process. This research analysed the effect of evaporation time, annealing temperature and annealing time on the average diameters, the distribution of particle size and the atom content of the material source of metal catalyst particles. The material that was used as the source of catalyst particles in this experiment was nickel (Ni) which is known to be suitable and easy to grow CNT. Nickel was deposited on object glass using the evaporation method to produce a thin layer of Ni. The variations of evaporation time were 25 s, 50 s and 75 s. The Ni catalyst film was then annealed with different variations of annealing temperatures and annealing times. The variations of annealing temperature and annealing time that were used were on 300°C, 400°C, 500°C and 2,5 hours, 3,5 hours, 4,5 hours. Catalyst particles that formed after evaporation and annealing process then were characterized using SEM and EDS. From SEM data analysis, it was concluded that the increasing of evaporation time made the average of particle diameter became larger and the distribution of particles size was better. The increasing of annealing temperature also made the average of particle diameter became larger but the distribution of particles size was decrease, meanwhile the increasing of annealing time improved the distribution of particles size and for relatively longer annealing time the average of nickel particle diameter was able to be smaller. EDS results showed that the nickel atom content on the samples increased as the rise of evaporation and annealing time, while nickel content decreased as the increasing of annealing temperature. The optimal evaporation and annealing parameters to prepare the particles of Ni metal catalyst in this study was proposed in evaporation time of 50 s, annealing temperature of 500°C and annealing time of 4,5 hours.